Knowledge, attitude, and practice of contraceptives among women in Kuantan - Abdul Rashid, Nor'ain; Muhammad Rafi Ravi, Jezreen Syaza; Jamil, Nurul Akma; Muhammed, Auwalu (Universiti Sultan Zainal Abidin (UniSZA), 2025)
Global challenges in family planning and contraceptive use often lead to unintended pregnancies, unsafe abortions, and adverse maternal and child health outcomes. These issues are frequently attributed to insufficient knowledge, negative attitudes, and limited contraceptive practices among women. Assessing contraceptive knowledge, attitudes, and practices (KAP) in Kuantan is therefore essential. This study aimed to evaluate KAP regarding contraceptives among women in Kuantan and to explore the relationship between sociodemographic factors and these KAP dimensions. A cross-sectional study was conducted using self-administered questionnaires among 319 women in Kuantan, Pahang, through a convenience sampling method. Data were analysed using descriptive statistics, Pearson's Chi-Square test, and Fisher’s Exact test via SPSS version 27.0. A p-value of less than 0.05 was considered statistically significant. The mean (±SD) age of the participants was 33.66 (±6.74). Nearly all participants (99.4%) were aware of contraceptives, and most (96.2%) showed a positive attitude regarding contraceptives. A substantial majority (82.8%) of participants reported using contraceptives, with pills being the most common method (49.4%). Concerns about side effects were the main reason cited for not using contraceptives. Additionally, there was a significant association between low number of children and high used of contraceptive (p=0.003). Overall, most of the women exhibit high awareness, positive attitudes towards contraceptives, and widespread usage of them. Further research is recommended in rural areas to gain better insight regarding their KAP of contraceptives.